Teaching practice with students with special necessities? (Praxis Educativa, 2012)
This paper is part of one of the extension projects carried out by the Chair of Clinical Psychopedagogy, University of Comahue logether with some professionals from the Technical Team of Pedagogic Support (Rio Negro's Board of Education) with the aim of focusing on that part of the students' population, which was not receiving support from these teams and was labeled “With Special Educational Needs” Upon revision of the current legislation and after completion of the first interventions carried out (interviews to principals and teachers and class observations) we became aware of the need to focus on the particularities of teaching those students that show learning difficulties and do not receive attention from specialized teachers. What is the place that these students are offered? This paper introduces some considerations in relation to key points regarding teaching children with learning difficulties The role of teachers and children, and the need to consider diversity issues, among other variables, are explored.
Keywords: teaching practice; special educational needs; learning difficulties; subjectivity; diversity